Underwater channel design for diver communication - N, Reshma; Ramesh, T K (International Journal of Engineering and Technology, 2018)
Underwater channels are usually considered to be very difficult media for communication purposes. There are many reasons that pull back us from considering these types of channels for communication purposes. Limited bandwidth, Doppler effect, multipath propagation etc are some of those reasons. These reasons limit the usage of underwater channel for wide range of applications.Optical waves, RF waves and acoustic waves are generally used. Among the methods, acoustic waves are used in most of the cases since less attenuation and scattering properties are offered by acoustic waves. There are many acoustic channel models existing but require some improvisations according to the diving application. An efficient acoustic underwater channel for diver communication is designed and implemented in this paper. Rayleigh channel model is considered in our algorithm that can deal with multipath propagation and Doppler effect with underwater specifications incorporated to it.This method gives a better result compared to OFDM and MIMO models. Further, a comparison between different modulation techniques like ASK, BPSK and QAM have been done. Results show QAM is a better modulation scheme for underwater environment.